(untitled) (Editora Impacto Científico, 2025)
Fishing stands out as one of the oldest activities carried out by humans, being essential for the subsistence of riverside families and an important source of income through the sale of fish. Communities that have fishing as their main activity organize themselves socially and spatially along the banks of rivers. However, with the advances of modernization and the environmental problems that have intensified in recent years, these communities face serious difficulties that profoundly affect their ways of life. This study aimed to analyze the socioeconomic conditions of fishermen in the Beira Rio community, located in the municipality of Peixoto de Azevedo (MT). The research followed a qualitative-quantitative approach, and information was collected through questionnaires administered directly to fishermen. The research stages included a literature review, fieldwork, systematization, analysis, and contextualization of the data. The results revealed that, among the interviewees, the majority are male. The participants have a low level of education, with ages ranging from 30 to 70 years. Their families are mostly composed of 4 to 9 members, surviving on a monthly income of one to two minimum wages. The socio-environmental vulnerability of these fishermen is directly related to the reduction in the number of fish in the Peixoto de Azevedo River, a process that profoundly impacts those who depend on fishing for their livelihood. This phenomenon is aggravated by deforestation in the region and mining activity, since the mines are located near the river.